2012
DOI: 10.1002/adma.201201464
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Enhancement of Hole Transport in Top‐Gated N‐Type Polymer Field‐Effect Transistors by a High‐k Dielectric for Ambipolar Electronic Circuits

Abstract: A remarkable enhancement of p-channel properties is achieved in initially n-channel dominant ambipolar P(NDI2OD-T2) organic field-effect transistors (OFETs) by the use of the fluorinated high-k dielectric P(VDF-TrFE). An almost two orders of magnitude increase in hole mobility (~0.11 cm(2) V(-1) s(-1) ) originates from a strong interface modification at the semiconductor/dielectric interface, which provides high-performance complementary-like inverters and ring oscillator circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
175
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 44 publications
7
175
0
1
Order By: Relevance
“…It should be noted that P(NDI2OD-T2) is a typical high-mobility n-type semiconductor with a low degree of energetic disorder (32) and both theoretical and experimental studies have shown intrinsically unbalanced electron and hole transport properties in low (i.e., diodes) and high (i.e., OFETs) charge density regimes (33). However, when fluorinated, high-k gate polymers are used as a dielectric insulator, both electrons and holes can be accumulated in the channel, leading to balanced ambipolarity (34,35). The dielectric used here is a 600-nm-thick poly(trifluoroethylene) (PTrFE) film.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that P(NDI2OD-T2) is a typical high-mobility n-type semiconductor with a low degree of energetic disorder (32) and both theoretical and experimental studies have shown intrinsically unbalanced electron and hole transport properties in low (i.e., diodes) and high (i.e., OFETs) charge density regimes (33). However, when fluorinated, high-k gate polymers are used as a dielectric insulator, both electrons and holes can be accumulated in the channel, leading to balanced ambipolarity (34,35). The dielectric used here is a 600-nm-thick poly(trifluoroethylene) (PTrFE) film.…”
Section: Resultsmentioning
confidence: 99%
“…36 Similar phenomena have also been observed in organic semiconductors. [37][38][39] Although the exact Fermi energy levels and the depletion region lengths of PbS QD and IGZO are unknown, the conceptual energy band diagram of the p-PbS/n-IGZO junction in Figure 3d illustrated the photogenerated charge transfer processes well. To further clarify this working mechanism, time-resolved photoluminescence (TRPL) experiments using the time-correlated singlephoton counting technique (TCSPC) were carried out.…”
Section: Phototransistor Characteristicsmentioning
confidence: 99%
“…However, there are very few choices of suitable polymer dielectrics with high enough k values. Cyanoethylpullulan (CYEPL) [75], ferroelectric polymer poly (vinylidenefluoride-trifluoroethylene) [P(VDF-TrFE)] [76], and relaxor ferroelectric polymer poly(vinylidene fluoridetrifluoroethylene-chlorofloroethylene) [P(VDF-TrFE-CFE)] [77], [78] have been studied for lowvoltage OTFTs. P(VDF-TrFE-CFE) was reported to have a k value above 60 [78].…”
Section: Review Of Current Statusmentioning
confidence: 99%